High-resolution hydraulic modelling as an approach to planning rehabilitation interventions in unchanneled valley-bottom palmiet wetlands: a case study of the Kromme River - Langner, Wiebke (Rhodes University, Faculty of Science, Department of Geography)
This study employs high-resolution hydraulic modelling techniques to inform the planning of rehabilitation interventions in unchanneled valley-bottom palmiet wetlands, using the upper Kromme River wetlands as a case study. It investigates the impact of geomorphic processes on the morphology of the valley, how changes in valley morphology affect the flow characteristics (velocity, stream power, depth) of the river, and how these changes affect the geomorphic dynamics of the wetlands. An aerial LiDAR survey was conducted for a 23km-long reach of the upper Kromme River where the wetlands are situated. A high-resolution (5 m) DTM was created from the LiDAR data to examine the valley morphology. Focusing on three major wetland basins, the relationship between valley morphology and geomorphic processes was examined using high-resolution imagery that accompanied the LiDAR survey and Google Satellite imagery. The hydraulic modelling software HEC-RAS was used to investigate the spatial variation in velocity, stream power, and water depth down the surveyed length of the river. The model outputs provide insight into the effect of valley morphology on flow characteristics. The river appears to have a graded longitudinal profile, such that there is a systematic reduction in slope down its length. Water flowing down the river works, through the processes of erosion and deposition, to control the longitudinal slope, channel planform, and geometry to create a valley with a gentle longitudinal slope (approximately 1%) and a broad, near-horizontal valley-bottom in the mountainous landscape of the Cape Fold Mountains. The overall form of the Kromme River valley and wetlands is primarily a consequence of repeated cycles of cutting and filling. Tributary alluvial fans control the initiation of gully erosion in the wetlands, but their effect is diminished in a downstream direction. Despite a 10-fold increase in discharge down the 23km length of river for a given flood magnitude, there is no significant increase in flow velocity, stream power, or depth in a downstream direction. Consequently, the kinetic energy of the water in the lower wetland basin is surprisingly low. These conditions favour the establishment of palmiet. Flows in eroded reaches are much higher than in non-eroded reaches where discharge is spread across a broad valley bottom. In terms of palmiet establishment and regeneration, this means that areas dominated by depositional processes are best suited to the establishment of palmiet. Based on this information, optimal sites to trial new wetland rehabilitation strategies that employ palmiet were selected. This work supports the importance of understanding the role of geomorphology in wetland structure and dynamics when approaching wetland rehabilitation and is likely to be more sympathetic to natural processes than current interventions.
Keywords: Hydraulic models; Prionium serratum; Wetland conservation -- South Africa Kromme River (Eastern Cape); LiDAR; Fluvial geomorphology